TOPICAL ISSUES IN THE IMPLEMENTATION OF CLOUD SERVICES FOR DATA HANDLING - KYSIUK, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the relevance of implementing cloud services as a key tool for organizing work with large amounts of data (Big Data) in the context of digital transformation of enterprises. The emphasis is on the growing demand for cloud technologies in the context of globalization, dynamic development of the information environment and the need for flexible data processing regardless of time, place and device. The historical prerequisites for the emergence of cloud technologies, their current state and growth trends of the cloud computing market are outlined. Special attention is paid to the classification of cloud services according to the IaaS, SaaS, BaaS, KaaS models, their functional purpose, technical capabilities, advantages and application options are described. Examples of implementing cloud technologies in various areas, such as the financial sector, education, medicine and trade, are highlighted. It is noted that cloud platforms provide a high level of automation, integration with virtualization tools, data protection, support for containerization and self-service. Three main scenarios for implementing cloud solutions are revealed: creating your own infrastructure, combined technology platforms, and using ready-made solutions from providers. It is shown that the implementation of hybrid clouds allows enterprises to achieve a balance between security, cost, and productivity. The role of cloud technologies in increasing operational efficiency, improving analytical capabilities, and decision-making is described. At the same time, the main risks are identified: privacy threats, storage overload, and reduced analytics efficiency due to an excess of irrelevant information. The conclusion is made about the strategic importance of cloud platforms in the context of innovative development and data management in the context of global digitalization.